Biomechanical and clinical evaluation of PSO, modified PSO and VCR treating OVCF kyphosis: a finite element analysis - Li, Junyu; Xu, Lizhi; Wang, Haotian; Liu, Yinhao; Sun, Zhuoran; Wang, Yongqiang; Yu, Miao; Li, Weishi; Zeng, Yan (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: To confirm the effect of surgery on spinal column biomechanics and to provide theoretical support for the differences in complications.Methods: 33 continuous patients with no significant difference in risk factors related to the complications were enrolled in this retrospective study. Sagittal parameters were measured in the pre-, post-operative and following-up orthostatic flat films. An finite element(FE) model was created using CT scanning from a female volunteer with osteoporotic vertebral compression fracture(OVCF) but no other severe spinal deformities. Pedicle subtraction osteotomy(PSO), vertebral column resection(VCR) and modified PSO(mPSO) for OVCF were simulated on FE model. Stress distribution characteristics, load sharing, strain displacement and strain angle change were measured.Results: Clinical -All differences in preoperative spinal sagittal parameters were not statistically significant. mPSO showed it is superior to PSO and VCR in multiple postoperative and following-up spinal sagittal parameters. The operation duration and intraoperative blood loss of mPSO are less than the other two. For postoperative complications, no statistically significant differences were observed. Biomechanical -Six operating conditions (flexion, extension, left/right bending, left/right twisting) for each post-operative FE model have been examined. In most conditions, the displacement of mPSO is similar to that of PSO, with both larger than that of VCR. All the maximum equivalent stress on the vertebral body is within the safe range. The stress is mainly distributed on the T10 vertebral body and the fixed vertebral body L2, while the stress of VCR is greater than that of mPSO and PSO. The intervertebral disc pressure is highest in VCR, followed by PSO, and lowest in mPSO under all conditions. The maximum pressure on the intervertebral discs is located between T10 and T11.Conclusions: The finite element analysis showed that mPSO has a similar spine stability to PSO, and possibly creates a better environment for bone-to-bone fusion and prevents adjacent segments degeneration. Combined with its smaller surgical risks, we believe that the modified pedicle subtraction osteotomy may be an appropriate surgical intervention for indicated cases of OVCF.